2021
DOI: 10.1128/jvi.00530-21
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 Regulates Vaccine-Induced Mucosal T-Cell Memory to Influenza A Virus

Abstract: Elicitation of lung tissue-resident memory CD8 T cells (TRMs) is a goal of T-cell based vaccines against respiratory viral pathogens, such as influenza A virus (IAV). Chemokine receptor 2 (CCR2)-dependent monocyte trafficking plays an essential role in the establishment of CD8 TRMs in lungs of IAV-infected mice. Here, we used a combination adjuvant-based subunit vaccine strategy that evokes multifaceted (TC1/TC17/TH1/TH17) IAV nucleoprotein-specific lung TRMs, to determine whether CCR2 and monocyte infiltratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
3
5
0
Order By: Relevance
“…Further supporting a hybrid cell state, we independently confirmed the presence of a subset of granuloma T cells expressing both T-bet and RORα by flow cytometry ( Grant et al., 2022 ). Notably, although Th1 ∗ and ex-Th17 subsets are described primarily as CD4 T cells ( Darrah et al., 2020 ; Gideon et al., 2015 ; Lyadova and Panteleev, 2015 ; Mpande et al., 2018 ), our T1-T17 sub-cluster was characterized by the expression of both CD4 and CD8A/B transcripts ( Figures 3 C, 4 A–4C, S4 D, and S4E), suggesting that this phenotype is not an identity program but context dependent, consistent with findings in other systems ( Lee et al., 2021 ).
Figure 4 Phenotypic Diversity in T1-T17 cells (A) T1-T17 subcluster overlaid on unified T/NK cell cluster (left) and colored by normalized expression values for T1-T17 subcluster-defining genes (bold outlined boxes) and non-enriched canonical Type1 and type 17 genes (right).
…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Further supporting a hybrid cell state, we independently confirmed the presence of a subset of granuloma T cells expressing both T-bet and RORα by flow cytometry ( Grant et al., 2022 ). Notably, although Th1 ∗ and ex-Th17 subsets are described primarily as CD4 T cells ( Darrah et al., 2020 ; Gideon et al., 2015 ; Lyadova and Panteleev, 2015 ; Mpande et al., 2018 ), our T1-T17 sub-cluster was characterized by the expression of both CD4 and CD8A/B transcripts ( Figures 3 C, 4 A–4C, S4 D, and S4E), suggesting that this phenotype is not an identity program but context dependent, consistent with findings in other systems ( Lee et al., 2021 ).
Figure 4 Phenotypic Diversity in T1-T17 cells (A) T1-T17 subcluster overlaid on unified T/NK cell cluster (left) and colored by normalized expression values for T1-T17 subcluster-defining genes (bold outlined boxes) and non-enriched canonical Type1 and type 17 genes (right).
…”
Section: Resultssupporting
confidence: 87%
“…Aspects of these data are consistent with recent observations that granulomas established in immune-primed environments—e.g., existing Mtb infection ( Cadena et al., 2018 ) or intravenous or intrabronchial BCG vaccination—are characterized by Th1/17 expression patterns that are associated with protection ( Darrah et al., 2020 ; Dijkman et al., 2019 ); however, we extend these findings, defining appreciable substructure among the T1-T17 subcluster of relevance to control. The CD4 T1-T17 subpopulation (subpopulation 1) is most consistent with published descriptions of Th1/17 cells (e.g., Th1 ∗ or ex-Th17) ( Acosta-Rodriguez et al., 2007 ; Amezcua Vesely et al., 2019 ; Becattini et al., 2015 ; Lee et al., 2021 ; Lindestam Arlehamn et al., 2013 ; Mahnke et al., 2013 ; Nikitina et al., 2018 ). These cells could represent precursors to long-lived tissue memory, which has been shown to play a crucial protective role in autoimmunity, bacterial control, and memory immune responses to pathogens ( Amezcua Vesely et al., 2019 ; Liang et al., 2015 ; van Hamburg and Tas, 2018 ; Wacleche et al., 2016 ), including Mtb infection.…”
Section: Discussionsupporting
confidence: 87%
“…Unexpectedly, BATF, which is not a classical immune-related TF, showed the greatest increase in activity upon infection. Our results thus suggest that BATF likely plays a previously unappreciated role in the macrophage response to flu infection, paralleling its already established role in the induction of effector programs and epigenetic landscape of CD8 + T cells and innate lymphoid cells infected with flu (Wu et al 2022;Lee et al 2021;Scott-Browne et al 2016). Collectively, our results show that transcriptional and epigenetic changes in response to flu infection are highly coordinated and likely driven by the activation of infection-induced TFs involved in the regulation of antiviral responses.…”
Section: Transcriptional and Epigenetic Response To Influenza Infectionsupporting
confidence: 68%
“…Specifically, upon subcutaneous vaccination of mice, ADJ elicited effector CD8 T cells that differentiated into a distinct subset of granzyme B-expressing CD27 LO ‘effector-like’ memory CD8 T cells, which provided highly effective immunity to intracellular bacteria L. monocytogenes in spleen and liver ( 222 ). Additionally, we have reported that ADJ, in combination with TLR agonists CpG and GLA, stimulated high numbers of tissue resident memory CD4 and CD8 T cells in the respiratory tract and protected against antigenically distinct strains of influenza viruses ( 218 220 ). Recently, Kingstad-Bakke et al.…”
Section: Adjuvants and Cross-presentationmentioning
confidence: 99%
“…Like vaccine adjuvants, various innate immune cells, including monocytes, neutrophils, and conventional dendritic cells, are rapidly recruited within 24-48 hours of intradermal, intraperitoneal, and intranasal vaccination of ADJ-containing vaccines at the injection sites ( 219 , 222 , 230 ). CD8 T cell response induced by mucosal or parenteral administration of vaccine antigens formulated in ADJ was ablated in BATF-3-deficient mice ( 220 , 222 ). These data suggest that stimulation of CD8 T cell responses to subunit vaccine antigens formulated in ADJ requires cross-presentation, presumably by BATF3-dependent conventional migratory DCs.…”
Section: Adjuvants and Cross-presentationmentioning
confidence: 99%